Influence of pH and ionic strength on the floc-magnetic separation: Selective flocculation of fine iron ore - Junhyun Choi; Sang Bae Kim (Results in Engineering, 2023)
This study proposes the application of floc-magnetic separation to enhance the recovery of fine iron (Fe) ores from the Musan mine. The X-ray diffraction analysis revealed the predominant composition of raw samples to be magnetite (Fe3O4) and quartz (SiO2). Conventional magnetic separation indicated an increasing efficiency of Fe separation with increasing magnetic intensity. However, this method exhibited shortcomings in effectively separating fine particles. Consequently, supplementary floc-magnetic separation was undertaken. The introduction of sodium oleate and kerosene as flocculants increased the efficiency of Fe separation. This enhancement was attributed to the alteration of the hydrophobic surface properties of fine iron particles, leading to the formation of larger aggregates that could be readily separated. Furthermore, floc-magnetic separation was performed in the presence of salt solutions. The heightened ionic strength facilitated the aggregation of iron fine particles by compressing the electrical double layer around them. This reduction in the energy barrier between iron fine particles and flocculants facilitated a more favorable interaction in the presence of salt solutions than in their absence. The experimental findings indicate that the floc-magnetic separation method reinforced by the addition of flocculants and salt solutions demonstrates enhanced efficiency in separating iron minerals from raw ores. This is particularly notable for addressing the challenge posed by fine particles that remained unresolved in conventional magnetic separation processes.